2016
DOI: 10.1177/0886260515587667
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intimate Partner Violence Exposure on the Maternal Bond and PTSD Symptoms of Children

Abstract: The quality of the maternal bond can be disrupted in women exposed to intimate partner violence (IPV), causing them to be less available to their children. The aim of this study was to examine difficulties in emotional regulation in women exposed to IPV and the impact of IPV on both the maternal bond and posttraumatic symptoms among children. A cross-sectional study was carried out with two groups: IPV dyads ( n = 36) comprising mothers who had been exposed to IPV and their children, and control dyads ( n = 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 41 publications
0
20
1
2
Order By: Relevance
“…When women encounter violence from their partners, the care they provide for their children decreases. When violence happens, it has a persistent negative psychological effect on the victims [ 16 , 24 , 25 ], weakening the mother-child bond [ 21 , 26 ] and making women less autonomous [ 11 , 27 ]. When caregivers mind is occupied by negative thoughts that could be associated with some mental health problems, and their productivity and care to their children decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When women encounter violence from their partners, the care they provide for their children decreases. When violence happens, it has a persistent negative psychological effect on the victims [ 16 , 24 , 25 ], weakening the mother-child bond [ 21 , 26 ] and making women less autonomous [ 11 , 27 ]. When caregivers mind is occupied by negative thoughts that could be associated with some mental health problems, and their productivity and care to their children decrease.…”
Section: Discussionmentioning
confidence: 99%
“…For women who had given birth, the mean parity was 4.10 (SD ± 2.52) births. The age at marriage of 36% of the women were below 18 years, 56% of the women had In the past year 77 (18) 157 (18) 234 (18) Currently working 118 (28) 223 (25) 340 [21] a Widowed, divorced, and separated more than one child under the age of 5 years, and 6% of the women were pregnant during the survey (Table 2).…”
Section: Reproductive Characteristics Of Mothers/caregiversmentioning
confidence: 99%
“…In addition, it is possible that for traumatized parents, self-reported warmth is a less reliable measure than for non-traumatized parents, thereby limiting our ability to observe what could otherwise be an important effect. Nevertheless, a number of studies do support the use of self-reported parental warmth in traumatized parents (e.g., Gonçalves Boeckel, Wagner, & Grassi-Oliveira, 2015; Lavi & Slone, 2012). Still, there is a wide recognition of the importance of social support in maintaining physical and psychological health in at-risk populations (Brewin, Andrews, & Valentine, 2000; Cobb, 1976; Ozbay, Fitterling, Charney, & Southwick, 2008), indicating the relevance for further investigation of the long-term effects of all aspects of the child–mother relationship on the ability to benefit from social buffering.…”
Section: Discussionmentioning
confidence: 99%
“…The victimization of mothers and children is closely linked, with the victimization affecting the relationships between mothers and children (Lapierre et al 2018). The relationship between the mother's symptom and the children's symptoms indicates that the care actions of these mothers are impaired by the IPV that they suffered due to them being less available (Boeckel et al 2017).…”
Section: Discussionmentioning
confidence: 99%